MANAJEMEN TENAGA PENDIDIK BERBASIS KINERJA DI SEKOLAH LABORATORIUM PERCONTOHAN (LABSCHOOL) - Ekka Suryapriadi, Yudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2020)
Teacher management is very important in every institution in order to regulate the activities carried out, schools as educational organizations really need the management of teachers that are carried out properly. This study aims to review, analyze and describe the implementation of performance based teacher management oriented to improving the quality of teaching and learning activities (TLA). The method used is qualitative with research subjects are management officials, BPS (School Management), School Principal, Curriculum vice principal and classroom teachers and subject teachers. Research location at SD Labschool UPI. Data obtained through document review guidelines, interview guidelines, observation guidelines and self assessment. Data processing and analysis is done through the steps: data categorization and classification, data verification, data validation, member check, description of research results, and analysis and discussion of research results. The results showed that SD Labschool had the status of UPI academic supporting elements that developed educational innovations, educational management practices, and learning models, and carried out community service. SD Labschool is in the management of a one roof school management system and share authority and responsibilities between UPI and the Bandung Education Office (share authority and responsibility of school management system), teacher status is permanent teachers BPS (GT BPS), analysis of teacher needs based on on competence, teaching load, number of existing teachers, school programs, recruitment, distribution and placement of teachers is done at any time based on needs, the teacher shows good performance from preparation, implementation to evaluation of learning.